ANALISIS KINERJA KEUANGAN BANK SEBELUM DAN SETELAH MERGER-AKUISISI DI INDONESIA PERIODE 2000-2011 - Marcelia Stephanie Adriaans; Henrycus Winarto; Eko Walujo Suwardyono (Jurnal Ekonomi dan Bisnis, 2015)
Globalization makes technology and information more developing. Along the development of the technology and information, business environment is being dynamic and can change so fast. In the banking sektor, to face dynamic business environment, the Bank needs to evaluation and correction the performance of the company so that the bank can survive in competition. Strategy bank to stay survive is merge, merger or acquisition.Indonesia in 2000-2011 there was 19 cases of merge. This study will be researched the bank's financial performance before and after the merger / acquisition and will be measured using CAMELS ratio. And to know the bank's financial performance, the CAMELS ratio will tested using Paired Samples Test. Result of study show that that after merger on  = 5% only LDR which have significant differences, but the other ratios no significant differences in financial performance of banks. So there is no positive improvement in the financial performance of the bank in Indonesia after merger/acquisition.